FAKTOR PENYEBAB KURANGNYA KETERAMPILAN SISWA DALAM BERNYANYI UNISONODI SMP NEGERI 11 PADANG - Geby Citra Arifin; Indrayuda (Universitas Negeri Padang, 2025)
This study aims to reveal the factors causing students' lack of skills in singing in unison at SMP Negeri 11 Padang. The type of research used is a qualitative method with a descriptive approach. The instrument for this research is the researcher themselves, assisted by writing tools and a camera. Data is collected through literature study, observation, interviews and documentation. The steps in analysing the data are data collection, data identification, data classification, data clarification and data description. The research results indicate that the lack of students' skills in singing in unison at SMP Negeri 11 Padang is caused by several main factors, namely the lack of teacher stimulation, lack of interest and motivation, lack of discipline, and lack of guided practice. Regarding the lack of teacher stimulation, music teachers have not provided varied and innovative learning stimuli, so students are less actively engaged in the unison singing process. As for the lack of students' interest and motivation, some students show a lack of enthusiasm towards unison singing lessons. Regarding the lack of student discipline, students' discipline during practice and learning has not been optimal. Finally, concerning the lack of guided practice, students rarely have the opportunity for structured practice under the direct supervision of a teacher. These factors influence each other and directly affect the low quality of students' unison singing results. Therefore, improving unison singing skills requires enhancements in teaching methods, learning motivation, discipline development, and the provision of guided practice.